A apropriação das TICs por extensionistas e agricultores familiares: possibilidades para o desenvolvimento rural - Silva, Marcela Guimarães e (2014)
The relationship between development and communication historically unfolded in different perspectives, and you can analyze it in public rural extension services, since in Brazil were one of the main strategies for consolidation of development projects. It was in this scenario that the media have taken important both in broadcasting and information technologies to the field, as in the relationship between farmers and extension workers, the latter agents of state intervention, marking the passage of a diffuser model for the dialogical practices of rural extension. Thus, the problem of this research considers the advancement of new media (internet and mobile phone) before his popularity and the possibility of participation to represent individuals in the communication process, in a context where emerging new public policies on rural extension digital inclusion and family farming. And it aims to understand the significance of new information and communication technologies, ICTs, from its ownership in the relationship between extension workers and farmers under rural development. Therefore, a field research with the main theory of referential communication Muniz Sodré (2002) who argues that communication in mediated society covers issues about social connection and consumption of vehicles, thus focusing on a new form of cognitive perception and interpretation of the world by individuals. These aspects were used as categories of interpretation and analysis of the results obtained in field research conducted through semi-structured interviews with scripts and observation of everyday extension of the five municipal office EMATER / RS - ASCAR and 16 farmers of São Borja, West Frontier in the state. Faced with the reality studied it was observed that both traditional media such as ICTs are embedded in the routines of these individuals, representing the expansion of its social relations, the reorganization of their practices and the inclusion of women in the management of family property. Finally, it was concluded that ICTs in the relationship between farmers and extension mean new bonds, increasing access to information by groups, and especially the repositioning of each of these actors in the context of rural development, this is considered as a process of social change that requires the involvement of agents in their context.